Bird Community in Six Successional Stages of Habitats in Manokwari, Papua - Warmetan, Hermanus; Mulyani, Yeni A.; Mardiastuti, Ani; Rushayati, Siti B. (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Succession after disturbance can affect the response of the bird community at each stage of habitat succession. Research on the impact of succession on birds has never been done in Papua, so this research is needed to understand how birds can survive habitat changes. This study aimed to analyze bird communities and their responses to successional stages of habitats, i.e., shrubs, agriculture, mixed plantation forest, young secondary forest, old secondary forest, and primary forest. Data collection was done from January 2023 to October 2023. Bird data (species and numbers) were collected using the point count method. Vegetation data (species and density) were collected by using the plot method, and abiotic data (air temperature, humidity, and light intensity) were collected using a dry-wet thermometer and a lux meter. The Shannon-Wiener diversity indices (H') were calculated for birds and trees. Correlation of the bird data against habitat and abiotic parameters was calculated. There were 11,272 birds from 55 species belonging to 25 families in the study area. The young secondary forest had the highest bird number and diversity (44 species; H' = 3,424), in line with the Intermediate Disturbance Hypothesis. Bird communities generally have a strong correlation with vegetation but a weak correlation with abiotic data. In light of conservation importance, young secondary forest held the highest bird species richness, while the primary forest provided habitat for some species that are highly dependent on natural forests.